Case Report: Application of accelerated continuous theta burst stimulation in treatment-resistant depression - Sun, Guilan; Shen, Zhongxia; Wang, Minmin; Zhang, Xiaomei (Frontiers in Psychiatry, 2025)
Treatment-resistant depression (TRD) poses a significant challenge in psychiatric practice. While repetitive transcranial magnetic stimulation (rTMS) has emerged as a promising non-invasive neuromodulation technique for TRD, a subset of patients fails to respond adequately to these traditional rTMS protocols. This case report describes the treatment course of a 53-year-old female patient with a complex psychiatric history. Despite initial successful treatment and remission, the patient experienced a relapse of severe depression characterized by sleep disturbances, anxiety, anhedonia, and suicidal ideation. The patient underwent multiple pharmacological treatments, intermittent theta burst stimulation (iTBS) and electroconvulsive therapy (ECT) with limited success over the course of two years. Subsequently, the patient received accelerated continuous theta burst stimulation (a-cTBS) targeting the right dorsolateral prefrontal cortex (DLPFC). Following a-cTBS treatment (18000 pulses each day for 5 consecutive days), the patient showed significant improvement in depressive and anxiety symptoms, as well as in cognitive functions. Remarkable clinical improvement was observed: the Montgomery Depression Rating Scale score decreased from 32 to 9, the Hamilton Anxiety Rating Scale score dropped from 20 to 6, and suicidal ideation decreased from 13 to 5, ultimately disappearing. The outcomes of this intervention suggest that a-cTBS may represent a viable alternative for patients with TRD who do not benefit from existing treatment modalities.